(3R,4R,5S)-5-(acetamidomethyl)-N-benzyl-3,4-dihydroxytetrahydrofuran-3-carboxamide - Punzo, F; Watkin, D; Simone, M; Fleet, G (2005)
The title compound, C15H20N2O 5, is the first example of a branched tetrahydrofuran sugar amino acid dipeptide isostere incorporated into a peptidomimetic. The crystal structure contains intermolecular N-H⋯O and O-H⋯O hydrogen bonds. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.